Sources of West Indian history - Augier, F.R. (Longmans LondonGB, 1962)
Contains a collection of various accounts written about many of the events which have taken place in the West Indies. Includes accounts taken from official papers such as the despatches between governors and the British Government, debates and laws of the West Indian legislatures, and reports of officials; from private papers, such as letters, journals and diaries; from books published at the time of the events or conditions they discuss; from contemporary newspapers; and from public petitions.